1994
DOI: 10.1111/j.1423-0410.1994.tb05040.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Low‐Frequency Red Cell Antigen, ‘SARAH’

Abstract: There are more than 100 low-frequency antigens (LFAs) which have been given International Society of Blood Transfusion (ISBT) numbers as members of systems, collections or the 700 series. In addition, there are a number of well-known (to reference laboratories) unpublished LFAs. The presence of an LFA was suspected when 2 sera were found to react with a single example of K homozygous cells. Anti-K reacting with K homozygotes was eliminated on testing with other KK cells. Testing of the reactive cell with antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…At first sight, these findings are in contrast with the original publication, which suggested that SARA was not an MNS blood group antigen as the SARA antigen is resistant to ficin and papain treatment while many MNS antigens, including M, N, Vw, Hut, Mur, M g , Vr, Hop, Bun, Mut, and Os a , are sensitive to treatment by these enzymes . However, this can be explained as on the glycophorin A molecule, Gly78 is a ficin proteolytic site and Arg80 is a papain proteolytic site.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…At first sight, these findings are in contrast with the original publication, which suggested that SARA was not an MNS blood group antigen as the SARA antigen is resistant to ficin and papain treatment while many MNS antigens, including M, N, Vw, Hut, Mur, M g , Vr, Hop, Bun, Mut, and Os a , are sensitive to treatment by these enzymes . However, this can be explained as on the glycophorin A molecule, Gly78 is a ficin proteolytic site and Arg80 is a papain proteolytic site.…”
Section: Discussionmentioning
confidence: 59%
“…The Wilcox serum is known to react with 20 low‐frequency Diego and glycophorin A antigens, including Dantu, Mt a , and Ri a . The original investigation into the SARA proband and family was undertaken using Wilcox serum . Based on the work performed by the original authors and consistent with our demonstration that SARA is a glycophorin A antigen, SARA should be added to the list of known specificities of this reagent.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…System 2: MNS Two antigens have been added to the MNS system. Exome sequence analysis of samples from SARA+ and SARA-family members [1] identified a single nucleotide change c.240G>T in exon 3 of GYPA, which changes p.Arg80Ser. Sequence analysis of unrelated SARA+ samples confirmed the causative polymorphism [2].…”
Section: New Blood Group Antigensmentioning
confidence: 99%